Preparation method of lead-free sodium niobate anti-ferroelectric ceramic material with low hysteresis and high electrostrictive strain and product prepared by preparation method

By introducing Sn and Ce ion doping modifications into lead-free sodium niobate antiferroelectric material, a lead-free sodium niobate antiferroelectric ceramic material with the chemical formula Na1-xNb1-xO3-0.5x-0.75xSnO2/CeO2 was prepared, which solved the problem of strain hysteresis of lead-free sodium niobate antiferroelectric in the prior art, and achieved the effect of low hysteresis and high electrostrain.

CN119751061APending Publication Date: 2025-04-04TONGREN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411921046.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing lead-free sodium niobate antiferroelectrics have a large strain hysteresis in electrogenic strain, which reduces the strain speed and service life of the material.

Method used

By introducing Sn and Ce ion doping modification, a lead-free sodium niobate antiferroelectric ceramic material with the chemical formula Na1-xNb1-xO3-0.5x-0.75xSnO2/CeO2 was prepared. Wet ball milling and multiple prefiring treatment were used to optimize the material's microstructure to reduce phase change hysteresis.

Benefits of technology

A lead-free sodium niobate antiferroelectric ceramic material with low hysteresis and high electrostrain has a large strain at room temperature at a lower electric field strength, and the phase change hysteresis is small and there is no negative strain.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751061A_ABST
    Figure CN119751061A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a lead-free sodium niobate anti-ferroelectric ceramic material with low hysteresis and high electrostrictive strain and a product prepared by the preparation method, and the lead-free sodium niobate anti-ferroelectric ceramic material with a main crystalline phase as an anti-ferroelectric phase, small phase change hysteresis and good strain performance is prepared by introducing two ions Sn and Ce for doping modification. The method is simple in process, environmentally friendly, safe, stable and controllable, the prepared ceramic material is an antiferroelectric enhanced sodium niobate antiferroelectric and has low hysteresis and high strain, the strain speed of the material is increased, the service life is prolonged, and progress and development of a lead-free antiferroelectric system technology are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional ceramic materials, and in particular to a preparation method of a lead-free antiferroelectric ceramic material and a product obtained therefrom. Background Art

[0002] When an external electric field is applied, the crystal structure of the material is distorted, and the phenomenon of macroscopic deformation is called electrostrain. The electrostrain effect is widely used in devices such as actuators, sensors and micro-displacement drives. According to the relationship between the strain of the material and the external electric field, it can be divided into the following four categories: (1) Typical ferroelectrics. The bipolar strain (SE) curve of a typical ferroelectric shows a symmetrical "butterfly" curve (see Figure 1 (a)), with large hysteresis and negative strain. (2) In an antiferroelectric, the electric field-induced phase transition from the antiferroelectric phase to the ferroelectric phase causes a huge change in the unit cell volume, which is conducive to obtaining a large strain but is accompanied by a large hysteresis (see Figure 1 (b)). The large strain and mechanical driving force of antiferroelectrics can be applied in the field of sensors and actuators. (3) Hard-doped ferroelectrics (low-valent elements replace high-valent elements), the bipolar SE curve has an asymmetric "butterfly" curve (see Figure 1 (c)), negative strain also exists. (4) Bipolar strain curve of relaxor ferroelectric (see Figure 1 (d)) There is no hysteresis and negative strain, and the strain is low.

[0003] Electrostrain mainly comes from two parts: intrinsic contribution and extrinsic contribution. The intrinsic contribution includes the inverse piezoelectric effect and the electrostrictive effect, and the extrinsic contribution includes the flipping of non-180° domains under the action of an external electric field and the electroinduced phase transition. The electroinduced phase transition includes the paraelectric-ferroelectric phase transition, the relaxor-ferroelectric phase transition and the antiferroelectric-ferroelectric phase transition. In antiferroelectrics, the hysteresis phase transition is the main source of strain. Under the action of an external electric field, a reversible transition between the antiferroelectric phase and the ferroelectric phase occurs, accompanied by a rapid expansion of the volume. Therefore, antiferroelectric materials are more suitable for large strain and high-power brakes. Lead-containing antiferroelectrics have a good strain capacity, but lead poses a great threat to human health and environmental safety, so countries have issued lead restrictions accordingly, and lead-free antiferroelectrics are imperative. In the lead-free antiferroelectric system, sodium niobate antiferroelectrics have the advantages of low price, simple process, and low density, making them a hot topic of research. Sodium niobate also has many shortcomings as an antiferroelectric. Pure sodium niobate does not show antiferroelectric properties, and its antiferroelectric phase can only be enhanced after formula design. Moreover, as an electrohysteresis strain material, the electro-induced strain of general antiferroelectrics has a large strain hysteresis, which reduces the strain rate and service life of the material. Therefore, it is very necessary to prepare an antiferroelectric-enhanced sodium niobate antiferroelectric through formula design, which has low hysteresis and high strain. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a lead-free sodium niobate antiferroelectric ceramic material with low hysteresis and high electro-strain, and to prepare a lead-free sodium niobate antiferroelectric ceramic material with an antiferroelectric phase as the main crystal phase, small phase change hysteresis and good strain performance by introducing two ions Sn and Ce for doping modification. Another purpose of the present invention is to provide a product obtained by using the method for preparing the lead-free sodium niobate antiferroelectric ceramic material with low hysteresis and high electro-strain.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] The present invention provides a method for preparing a lead-free sodium niobate antiferroelectric ceramic material with low hysteresis and high electro-induced strain, wherein the chemical formula of the antiferroelectric ceramic material is Na 1-x Nb 1-x O 3-0.5x -0.75xSnO 2 / CeO 2 , wherein 0.01<x<0.08, preferably, 0.01<x≤0.04; the preparation method comprises the following steps:

[0007] (1) using niobium pentoxide, anhydrous sodium carbonate, tin dioxide, and cerium dioxide as raw materials, weighing them according to the chemical formula, and performing a wet ball milling process to obtain a mixed slurry;

[0008] (2) After the primary mixed slurry is dried and sieved, it is pressed into a shape and pre-calcined at a temperature of 850 to 950° C. for 4 to 8 hours. The resulting product is crushed and sieved to obtain a powder;

[0009] (3) The powder is subjected to a secondary wet ball milling process to obtain a secondary mixed slurry;

[0010] (4) the secondary mixed slurry is dried, sieved, granulated, aged, and pressed to obtain a green body;

[0011] (5) calcining the green body, i.e., heating the green body to 1000° C. at 5° C. / min, keeping the temperature for 30 to 60 min, and then heating the green body to 1200 to 1300° C. at 3° C. / min, keeping the temperature for 2 to 4 h, to obtain a lead-free sodium niobate antiferroelectric ceramic material.

[0012] Furthermore, the primary wet ball milling treatment and the secondary wet ball milling treatment of the present invention are to use anhydrous ethanol as a solution and zirconium oxide as a ball milling medium, and use a planetary ball mill at 30 to 40 Hz for 10 to 24 hours.

[0013] The product obtained by the preparation method of the lead-free sodium niobate antiferroelectric ceramic material with low hysteresis and high electrostrain has an antiferroelectric phase as the main crystal phase; under the electric field strength of 40-60 kV / cm and the frequency of 1-10 Hz, the maximum positive strain is 0.14-0.48%.

[0014] The present invention has the following beneficial effects:

[0015] (1) The present invention introduces two ions Sn and Ce for doping modification, and the prepared lead-free sodium niobate antiferroelectric ceramic material has an antiferroelectric phase as the main crystal phase, and exhibits a double hysteresis loop at room temperature. The strain corresponding to the electric field strength of 60kV / cm at room temperature is close to 0.4%, the corresponding phase change hysteresis is small, and the negative strain is zero.

[0016] (2) The doped modified lead-free sodium niobate antiferroelectric ceramic material prepared by the present invention has good strain performance, the reason for which is that: Sn is Sn 2+ and Sn 4+ Exist at the same time, Ce with Ce 3+ and Ce 4+ Coexistence; Sn 2+ and Ce 3+ At the same time, Sn replaces the sodium ion at the A position of sodium niobate. 4+ and Ce 4+ At the same time, it replaces the niobium ion at the B position of sodium niobate. Sodium in sodium niobate has two positions. When the doping amount is low, Sn 2+ and Ce 3+ Instead of replacing one of the sodium ions in a random manner, Sn 2+ It forms a covalent bond with oxygen ions. In addition, ion substitution produces substitution defects to form defect dipoles. Under the action of covalent bonds and defect dipoles, sodium niobate is restored to its original antiferroelectric phase after the phase transition due to the applied electric field, so there is no obvious phase transition hysteresis in the electrostrain. The simultaneous action of covalent bonds and defect dipoles also reduces the phase transition barrier between the antiferroelectric and ferroelectric phases of sodium niobate, making the phase transition easier, and the material can undergo a complete phase transition before breakdown. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings:

[0018] Figure 1 are the bipolar strain (SE) curves of four ferroelectrics ((a): ferroelectric; (b): antiferroelectric; (c): hard-doped ferroelectric; (d): relaxor ferroelectric);

[0019] Figure 2The XRD spectrum, hysteresis loop and strain curve of the antiferroelectric ceramic material prepared in Example 1 of the present invention at room temperature (a: XRD spectrum; b: hysteresis loop; c: strain curve);

[0020] Figure 3 The XRD spectrum, hysteresis loop and strain curve of the antiferroelectric ceramic material prepared in Example 2 of the present invention at room temperature (a: XRD spectrum; b: hysteresis loop; c: strain curve);

[0021] Figure 4 The XRD spectrum, hysteresis loop and strain curve of the antiferroelectric ceramic material prepared in Example 3 of the present invention at room temperature (a: XRD spectrum; b: hysteresis loop; c: strain curve);

[0022] Figure 5 The XRD spectrum, hysteresis loop and strain curve of the antiferroelectric ceramic material prepared in Example 4 of the present invention at room temperature (a: XRD spectrum; b: hysteresis loop);

[0023] Figure 6 This is the hysteresis loop of the antiferroelectric ceramic material prepared in Example 5 of the present invention at room temperature. DETAILED DESCRIPTION

[0024] Embodiment 1:

[0025] This embodiment provides a method for preparing a lead-free sodium niobate antiferroelectric ceramic material with low hysteresis and high electro-induced strain. The antiferroelectric ceramic material has a chemical formula of Na 0.99 Nb 0.99 O 2.995 -0.0075SnO 2 / CeO 2 ; The preparation method comprises the following steps:

[0026] (1) using niobium pentoxide, anhydrous sodium carbonate, tin dioxide, and cerium dioxide as raw materials, weighing them according to the above chemical formula, and then performing a wet ball milling treatment, that is, using anhydrous ethanol as a solution and zirconium oxide as a ball milling medium, using a planetary ball mill at 30 Hz for 24 hours to obtain a primary mixed slurry;

[0027] (2) The primary mixed slurry is dried, passed through an 80-mesh sieve, pressed into a disc with a diameter of 5 cm, and pre-calcined at 900° C. for 6 h. The resulting product is crushed and sieved to obtain a powder;

[0028] (3) The powder was subjected to a secondary wet ball milling treatment, i.e., anhydrous ethanol was used as a solution and zirconium oxide was used as a ball milling medium, and the ball milling was performed at 30 Hz for 24 hours using a planetary ball mill to obtain a secondary mixed slurry;

[0029] (4) After the secondary mixed slurry is dried and passed through an 80-mesh sieve, 5 wt% of PVA is added and granulated using 60-mesh, 80-mesh and 120-mesh sieves; the granulated particles are aged and pressed into discs with a diameter of 13 mm to obtain green sheets;

[0030] (5) The green body is subjected to calcination treatment, i.e., the temperature is increased to 1000° C. at 5° C. / min, kept at this temperature for 30 min, and then the temperature is increased to 1270° C. at 3° C. / min, kept at this temperature for 2 h, to obtain a lead-free sodium niobate antiferroelectric ceramic material.

[0031] The antiferroelectric ceramic material prepared in this embodiment was thinned to 150-300 microns on both sides, and then covered with silver electrodes to test the corresponding electrical properties. Figure 2 As shown, the antiferroelectric ceramic material sample of this embodiment has a low phase transition barrier between antiferroelectric and ferroelectric, and a complete phase transition occurs at room temperature under a relatively low electric field (120 kV / cm), with a maximum strain of 0.16% and a negative strain close to zero.

[0032] Embodiment 2:

[0033] This embodiment provides a method for preparing a lead-free sodium niobate antiferroelectric ceramic material with low hysteresis and high electro-induced strain. The antiferroelectric ceramic material has a chemical formula of Na 0.96 Nb 0.96 O 2.98 -0.03SnO 2 / CeO 2 ; The preparation method comprises the following steps:

[0034] (1) using niobium pentoxide, anhydrous sodium carbonate, tin dioxide, and cerium dioxide as raw materials, weighing them according to the above chemical formula, and then performing a wet ball milling treatment, that is, using anhydrous ethanol as a solution and zirconium oxide as a ball milling medium, using a planetary ball mill at 30 Hz for 24 hours to obtain a primary mixed slurry;

[0035] (2) The primary mixed slurry is dried, passed through an 80-mesh sieve, pressed into a disc with a diameter of 5 cm, and pre-calcined at 900° C. for 6 h. The resulting product is crushed and sieved to obtain a powder;

[0036] (3) The powder was subjected to a secondary wet ball milling treatment, i.e., anhydrous ethanol was used as a solution and zirconium oxide was used as a ball milling medium, and the ball milling was performed at 30 Hz for 24 hours using a planetary ball mill to obtain a secondary mixed slurry;

[0037] (4) After the secondary mixed slurry is dried and passed through an 80-mesh sieve, 5 wt% of PVA is added and granulated using 60-mesh, 80-mesh and 120-mesh sieves; the granulated particles are aged and pressed into discs with a diameter of 13 mm to obtain green sheets;

[0038] (5) The green body is subjected to calcination treatment, i.e., the temperature is increased to 1000° C. at 5° C. / min, kept at this temperature for 30 min, and then the temperature is increased to 1270° C. at 3° C. / min, kept at this temperature for 2 h, to obtain a lead-free sodium niobate antiferroelectric ceramic material.

[0039] The antiferroelectric ceramic material prepared in this embodiment was thinned to 150-300 microns on both sides, and then covered with silver electrodes to test the corresponding electrical properties. Figure 3 As shown, the antiferroelectric ceramic material sample of this embodiment has a low phase transition barrier between antiferroelectric and ferroelectric, and a phase transition occurs under an electric field of 180 kV / cm at room temperature. The phase transition is reversible, the maximum strain is 0.38%, there is no negative strain, and the strain curve is slender.

[0040] Embodiment three:

[0041] This embodiment provides a method for preparing a lead-free sodium niobate antiferroelectric ceramic material with low hysteresis and high electro-induced strain. The antiferroelectric ceramic material has a chemical formula of Na 0.94 Nb 0.94 O 2.97 -0.015SnO 2 / CeO 2 ; The preparation method comprises the following steps:

[0042] (1) using niobium pentoxide, anhydrous sodium carbonate, tin dioxide, and cerium dioxide as raw materials, weighing them according to the above chemical formula, and then performing a wet ball milling treatment, that is, using anhydrous ethanol as a solution and zirconium oxide as a ball milling medium, using a planetary ball mill at 35 Hz for 18 hours to obtain a primary mixed slurry;

[0043] (2) The primary mixed slurry is dried, passed through an 80-mesh sieve, pressed into a disc with a diameter of 5 cm, and pre-calcined at 900° C. for 6 h. The resulting product is crushed and sieved to obtain a powder;

[0044] (3) The powder was subjected to a secondary wet ball milling treatment, i.e., anhydrous ethanol was used as a solution and zirconium oxide was used as a ball milling medium, and the ball milling was performed at 35 Hz for 18 hours using a planetary ball mill to obtain a secondary mixed slurry;

[0045] (4) After the secondary mixed slurry is dried and passed through an 80-mesh sieve, 5 wt% of PVA is added and granulated using 60-mesh, 80-mesh and 120-mesh sieves; the granulated particles are aged and pressed into discs with a diameter of 13 mm to obtain green sheets;

[0046] (5) The green body is calcined by heating the temperature to 1000° C. at a rate of 5° C. / min, keeping the temperature for 30 min, and then heating the temperature to 1250° C. at a rate of 3° C. / min, keeping the temperature for 2 h, to obtain a lead-free sodium niobate antiferroelectric ceramic material.

[0047] The antiferroelectric ceramic material prepared in this embodiment was thinned to 150-300 microns on both sides, and then covered with silver electrodes to test the corresponding electrical properties. Figure 4 As shown, the antiferroelectric ceramic material sample of this embodiment has a low phase transition barrier between antiferroelectric and ferroelectric, and phase transition occurs under an electric field of 190 kV / cm at room temperature, with a maximum strain of 0.14% and no negative strain.

[0048] Embodiment 4:

[0049] This embodiment provides a method for preparing a lead-free sodium niobate antiferroelectric ceramic material with low hysteresis and high electro-induced strain. The antiferroelectric ceramic material has a chemical formula of Na 0.98 Nb 0.98 O 2.99 -0.045SnO 2 / CeO 2 ; The preparation method comprises the following steps:

[0050] (1) using niobium pentoxide, anhydrous sodium carbonate, tin dioxide, and cerium dioxide as raw materials, weighing them according to the above chemical formula, and then performing a wet ball milling treatment, that is, using anhydrous ethanol as a solution and zirconium oxide as a ball milling medium, using a planetary ball mill at 30 Hz for 24 hours to obtain a primary mixed slurry;

[0051] (2) The primary mixed slurry is dried, passed through an 80-mesh sieve, pressed into a disc with a diameter of 5 cm, and pre-calcined at 900° C. for 6 h. The resulting product is crushed and sieved to obtain a powder;

[0052] (3) The powder was subjected to a secondary wet ball milling treatment, i.e., anhydrous ethanol was used as a solution and zirconium oxide was used as a ball milling medium, and the ball milling was performed at 30 Hz for 24 hours using a planetary ball mill to obtain a secondary mixed slurry;

[0053] (4) After the secondary mixed slurry is dried and passed through an 80-mesh sieve, 5 wt% of PVA is added and granulated using 60-mesh, 80-mesh and 120-mesh sieves; the granulated particles are aged and pressed into discs with a diameter of 13 mm to obtain green sheets;

[0054] (5) The green body is subjected to calcination treatment, i.e., the temperature is increased to 1000° C. at 5° C. / min, kept at this temperature for 30 min, and then the temperature is increased to 1270° C. at 3° C. / min, kept at this temperature for 2 h, to obtain a lead-free sodium niobate antiferroelectric ceramic material.

[0055] The antiferroelectric ceramic material prepared in this embodiment was thinned to 150-300 microns on both sides, and then covered with silver electrodes to test the corresponding electrical properties. Figure 5 As shown, the antiferroelectric ceramic material sample of this embodiment has a main crystalline phase of an antiferroelectric P phase and exhibits a typical double hysteresis loop at room temperature.

[0056] Embodiment five:

[0057] This embodiment provides a method for preparing a lead-free sodium niobate antiferroelectric ceramic material with low hysteresis and high electro-induced strain. The antiferroelectric ceramic material has a chemical formula of Na 0.96 Nb 0.96 O 2.98 -0.03SnO 2 / CeO 2 ; The preparation method comprises the following steps:

[0058] (1) using niobium pentoxide, anhydrous sodium carbonate, tin dioxide, and cerium dioxide as raw materials, weighing them according to the above chemical formula, and then performing a wet ball milling treatment, that is, using anhydrous ethanol as a solution and zirconium oxide as a ball milling medium, using a planetary ball mill at 40 Hz for 15 hours to obtain a primary mixed slurry;

[0059] (2) The primary mixed slurry is dried, passed through an 80-mesh sieve, pressed into a disc with a diameter of 5 cm, and pre-calcined at 900° C. for 6 h. The resulting product is crushed and sieved to obtain a powder;

[0060] (3) The powder was subjected to a secondary wet ball milling treatment, i.e., anhydrous ethanol was used as a solution and zirconium oxide was used as a ball milling medium, and the ball milling was performed at 40 Hz for 15 h using a planetary ball mill to obtain a secondary mixed slurry;

[0061] (4) After the secondary mixed slurry is dried and passed through an 80-mesh sieve, 5 wt% of PVA is added and granulated using 60-mesh, 80-mesh and 120-mesh sieves; the granulated particles are aged and pressed into discs with a diameter of 13 mm to obtain green sheets;

[0062] (5) The green body is calcined by heating the temperature to 1000° C. at a rate of 5° C. / min, keeping the temperature for 30 min, and then heating the temperature to 1250° C. at a rate of 3° C. / min, keeping the temperature for 2 h, to obtain a lead-free sodium niobate antiferroelectric ceramic material.

[0063] The antiferroelectric ceramic material prepared in this embodiment was thinned to 150-300 microns on both sides, and then covered with silver electrodes to test the corresponding electrical properties. The antiferroelectric ceramic material sample in this embodiment has a low phase transition barrier between antiferroelectric and ferroelectric, and a phase transition occurs under an electric field of 160 kV / cm at room temperature, and the phase transition is reversible, such as Figure 6 As shown, a typical double hysteresis loop is exhibited at room temperature.

Claims

1. A method for preparing a lead-free sodium niobate antiferroelectric ceramic material with low hysteresis and high electrostrain, characterized in that: The chemical formula of the antiferroelectric ceramic material is Na 1-x Nb 1-x O 3-0.5x -0.75xSnO2 / CeO2, wherein 0.01<x<0.08; the preparation method comprises the following steps: (1) using niobium pentoxide, anhydrous sodium carbonate, tin dioxide, and cerium dioxide as raw materials, weighing them according to the chemical formula, and performing a wet ball milling process to obtain a mixed slurry; (2) After the primary mixed slurry is dried and sieved, it is pressed into a shape and pre-calcined at a temperature of 850 to 950° C. for 4 to 8 hours. The resulting product is crushed and sieved to obtain a powder; (3) The powder is subjected to a secondary wet ball milling process to obtain a secondary mixed slurry; (4) the secondary mixed slurry is dried, sieved, granulated, aged, and pressed to obtain a green body; (5) calcining the green body, i.e., heating the green body to 1000° C. at 5° C. / min, keeping the temperature for 30 to 60 min, and then heating the green body to 1200 to 1300° C. at 3° C. / min, keeping the temperature for 2 to 4 h, to obtain a lead-free sodium niobate antiferroelectric ceramic material.

2. The method for preparing the lead-free sodium niobate antiferroelectric ceramic material with low hysteresis and high electrostrain according to claim 1, characterized in that: In the chemical formula, 0.01<x≤0.

04.

3. The method for preparing the lead-free sodium niobate antiferroelectric ceramic material with low hysteresis and high electrostrain according to claim 1, characterized in that: The primary wet ball milling treatment and the secondary wet ball milling treatment are performed by using anhydrous ethanol as a solution and zirconium oxide as a ball milling medium, and using a planetary ball mill for ball milling at 30 to 40 Hz for 10 to 24 hours.

4. A product obtained by the method for preparing a lead-free sodium niobate antiferroelectric ceramic material with low hysteresis and high electrostrain according to any one of claims 1 to 3, characterized in that: The main crystal phase of the antiferroelectric ceramic material is an antiferroelectric phase; under the conditions of an electric field strength of 40-60 kV / cm and a frequency of 1-10 Hz, the maximum positive strain is 0.14-0.48%.